Intraoperative findings and postoperative complications in laparoscopic cholecystectomy: the Greek experience with 5,539 patients in a single center. - Konstadoulakis, Manousos M; Antonakis, Pantelis T; Karatzikos, George; Alexakis, Nikolaos; Leandros, Emmanuel (J Laparoendosc Adv Surg Tech A, 2004)
BACKGROUND: This is a retrospective study presenting the experience of a teaching-oriented laparoendoscopic unit with laparoscopic cholecystectomy (LC) in order to add data to the international literature concerning issues such as epidemiology, intraoperative findings, conversion and complication rates. PATIENTS AND METHODS: In this study 5539 consecutive patients who underwent LC between 1990 and 2000 were included. Elective (n=4903) or emergent (n=636) LC was performed in all but 99 patients (who were converted to the open procedure). Conversion rate, complication rate, mortality, and length of stay were the main outcome parameters in this study. RESULTS: There was no intraoperative or in-hospital mortality in our series. The conversion rate was 1.8%. The complication rate was 2.92% (162 patients). The vast majority of our patients (92%) were discharged from the hospital on the first postoperative day. CONCLUSIONS: LC is a safe technique when up-to-date equipment and meticulous dissection techniques are employed. A specialized laparoscopic unit is important in a general surgery department, to have an experienced laparoscopic surgeon in all cases. In our opinion this is the only way to minimize common bile duct injuries and the rates of other major complications.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Cholecystectomy, Laparoscopic; Female; Greece; Humans; Intraoperative Period; Male; Middle Aged; Postoperative Complications; Retrospective Studies; Treatment Outcome